Successful anti‐viral treatment improves survival of patients with advanced liver disease due to chronic hepatitis C. Issue 6 (23rd January 2015) - Rutter, K.; Stättermayer, A. F.; Beinhardt, S.; Scherzer, T.‐M.; Steindl‐Munda, P.; Trauner, M.; Ferenci, P.; Hofer, H.
Summary Background Long‐term outcome of chronic hepatitis C patients with successful viral eradication seems to be promising. Aim To evaluate mortality, incidence of hepatocellular carcinoma (HCC), liver failure and liver transplantation in sustained virological responders (SVR) and non‐SVR patients with different stages of fibrosis. Methods Seven hundred and fourteen patients with a follow‐up of 7.2 (1–21.1) years (age: 51.4 ± 12.0 years, 276 female, IFN‐monotherapy: n = 19, IFN/RBV: n = 122, peg‐IFN/RBV: n = 573, SVR: 551, non‐SVR: 163) were studied. Two hundred and ten of 540 patients with a liver biopsy prior to treatment had advanced stages of fibrosis (Metavir F3/F4). Results Forty‐eight patients died during follow‐up, 15 with SVR and 33 without (P < 0.001). Five‐ and 10‐year mortality rates were 1.8% (10/551) and 2.7% (15/551) in the SVR group and 8.6% (14/163) and 19.1% (31/163) in the non‐SVR patients (P < 0.001). In 29 patients, decompensation of liver disease [SVR: 9 (1.6%) vs. non‐SVR: 20 (12.3%); P < 0.001] occurred and in 29 patients, HCC developed during follow‐up [SVR: 10 (1.8%) vs. non‐SVR: 19 (11.7%); P < 0.001]. Non‐SVR was an independent predictor for developing (i) HCC [HR: 2.36 (95% CI: 1.07–5.23; P = 0.034], (ii) liver‐related complications [HR: 2.62; (95% CI: 1.18–5.81; P = 0.018] and (iii) mortality (HR: 3.46; 95% CI: 1.91–6.29; P < 0.001). For patients with early stages of fibrosis (F0–F2), a survival benefit of SVR patients could not be demonstrated. Conclusions Successful anti‐viral therapy decreases mortality, incidence of hepatocellular carcinoma and liver failure in patients with advanced fibrosis. However, hepatocellular carcinoma development or liver failure are not prevented completely, and further follow‐up of patients is advisable.